TRANSNATIONAL REPRESSION:: PRINCIPLES AND CASE STUDIES - Túry, György (POLARITIES, 2023)
In this paper, I present and attempt to interpret transnational repression. It is not a completely new phenomenon, but it has some novel features and characteristics unique to the contemporary globalized world. They are the following: 1) the possibilities offered by information/communication technologies; 2) the constellations of power and repression that are shifting from physical space to virtual space; 3) the similarity of repressive practices and their global spread; 4) the role of bilateral or regional agreements; 5) the fact that powers, regardless of their political set-up, use techniques of transnational repression; 6) the phenomenon of authoritarian regimes integrating themselves into the global world order in such a way as to use and exploit aspects of the world order which they have been able to resist in order to legitimize their power; 7) the danger that transnational repression can undermine and amortize spaces, territories and systems from which it does not originate (cf. "new geographies of power").